WizardCoder: Empowering Code Large Language Models with Evol-Instruct - Luo, Ziyang; Xu, Can; Zhao, Pu; Sun, Qingfeng; Geng, Xiubo; Hu, Wenxiang; Tao, Chongyang; Ma, Jing; 林庆维, Qingwei Lin; Jiang (姜大昕), Daxin (ICLR 2024, 2023)
Code Large Language Models (Code LLMs), such as StarCoder, have demonstrated exceptional performance in code-related tasks. However, most existing models are solely pre-trained on extensive raw code data without instruction fine-tuning. In this paper, we introduce WizardCoder, which empowers Code LLMs with complex instruction fine-tuning, by adapting the Evol-Instruct method to the domain of code. Through comprehensive experiments on four prominent code generation benchmarks, namely HumanEval, HumanEval+, MBPP, and DS-1000, we unveil the exceptional capabilities of our model. It surpasses all other open-source Code LLMs by a substantial margin. Moreover, our model even outperforms the largest closed LLMs, Anthropic's Claude and Google's Bard, on HumanEval and HumanEval+. Our code, model weights, and data are public at https://github.com/nlpxucan/WizardLM